Multidisciplinary Sports Medicine Services: An Institutional Case Study of Indonesia Sport Medicine Centre - Anugrah Nur Warthadi; Muhammad Mirza Khabibi; Zakky Mafatihu Nur; Udesh Chaskar Bhaskaran (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study examines the institutional structure, operational mechanisms, service programs, and contributions of the Indonesia Sport Medicine Centre (ISMC) Jakarta in managing sports injuries and supporting national athletic performance. Methodology: A descriptive qualitative case study design was employed. Data were collected through in-depth semi-structured interviews with key institutional informants, direct field observations of ISMC facilities and operational processes, and systematic analysis of institutional documents including patient records and rehabilitation logs. Source triangulation and the Miles and Huberman interactive analysis model were applied to ensure validity and credibility of findings. Main Findings: ISMC operates as Indonesia’s first integrated private sports medicine clinic under PT Indonesia Sport Venture (ISV), supported by a multidisciplinary team of sports medicine specialists, physiotherapists, and sports science graduates. Core services include injury rehabilitation, Direct VO₂max testing, biomechanical and postural assessment (DIERS Formetric 4D), medical fitness, and corporate wellness. Between 2012 and 2015, ISMC treated 1,484 patients, including national athletes from multiple sports. Partnerships with PB PABSI, PRSI, PB Djarum, and PERSIB supported elite athlete screening and injury management. Novelty/Originality of this study: This study contributes to the limited literature on sports medicine institutions in Indonesia by providing an institutional analysis of ISMC integrated with recent developments in global sports medicine. The study highlights the strategic importance of multidisciplinary sports medicine systems in enhancing athlete rehabilitation, injury prevention, and national sports performance.